Development of radiation technologies on VNIIEF LU-10-20 linac - Zavyalov, N.V.; In’kov, V.I.; Lisovenko, N.A.; Punin, V.T.; Sitnikov, N.P.; Tarantasov, V.P.; Telnov, A.V.; Khohlov, Yu.A.; Shadrin, D.N.; Shorikov, I.V. (Вопросы атомной науки и техники, 1999)
In the present article there is given a review of a number of last works conducted at VNIIEF with the use of this accelerator.